A Narrative Review on Osteogenesis Imperfecta and Its Management - Asad Jamal Ansari; Guisia Khan; Kudshiya Khan (International Journal of Orthopedic Nursing and Practices, 2024)
Osteogenesis imperfecta (OI), sometimes referred to as brittle bone disease, is a heterogeneous illness characterized by short stature, several fractures, and distorted bones. The main contributing factor to OI is mutations in the genes needed to produce type 1 collagen. While severe OI is perinatally fatal, mild OI can occasionally not be detected until maturity. The frequency of Osteogenesis imperfecta ranges from about 1:15,000 to 1:20,000 births. Five kinds of the illness are commonly differentiated, ranging in severity from moderate (type I) to deadly (type II). Types III and IV are serious types that permit survival during the newborn period, but type V has a mild to moderate phenotype and interosseous membrane calcification. The majority of the time, mutations in the col I genes result in a decrease in the production of common type I collagen (col I) or the synthesis of uncommon collagen. Moreover, it has been shown that mutations in the genes responsible for osteoblast development, col I processing, and synthesis have occurred. The objective of this study is to review the research on the current medical treatments for osteogenesis imperfecta (OI) in patients. The treatments that are currently available aim to reduce or eliminate symptoms, prevent fractures, and build bone mass. Medications like bisphosphonates, denosumab, and teriparatide are frequently used to treat OI.
Keywords: Osteogenesis imperfecta; bisphosphonates; denosumab; physiotherapy; teriparatide